Nitric Oxide Levels in Erythrocyte of The Rabbits Which Implanted Ormocer Filling Materials into Connective Tissue - YILDIZ, MEHMET; UMUDUM, ZUHAL; TAYSI, SEYITHAN (Asian Journal of Chemistry, 2010)
The present aim of the study is to assess the alterations in nitric oxide (NO•) in erythrocytes of rabbits. NO• levels were measured in all groups. Erythrocyte NO• levels were of no significance in all comparisons. Ormocer filling materials do not cause an increase in reactive nitrogen species levels in erythrocytes of rabbits.